Pattern and Extent of Coronary Artery Disease in Patients of Ischemic Heart Disease aged 40 Years or less - Ahmed, Moeen Uddin; Hossain, Solaiman; Alam, M Shahidul; Parvez, Md Shahimur; Debnath, Debashish; Rahman Khan, Md Mahidur (Cardiovascular Journal, 2022)
Background: Atherosclerotic coronary artery disease is rare in young adults aged 40 years or less. However, South Asia is among the top 3 of the countries with highest proportion of cases of first acute coronary syndrome events occurring at age 40 years or less. This study was to explore the extent and pattern of angiographic coronary artery disease among patients of ischemic heart disease aged 40 years or less. Methods: This cross-sectional retrospective descriptive study included 140 patients who had coronary angiography for ischemic heart disease at the Department of Cardiology of Enam Medical College between July 2012 and December 2020. Coronary angiography was analyzed with particular attention to the extent of involvement of major epicardial coronary arteries including significant branch involvement. Results: Of the 140 patients included in the study - aged 18-40 years (mean 35.90 and SD 4.05) and 59.28% in the 36-40 years age group – 85% were male. Coronary angiogram revealed Single Vessel Disease in 39.29%, Double Vessel Disease in 25.72%, Triple Vessel disease in 23.57%, normal Coronaries in 9.28%. Left Anterior descending territory was most involved - 94 (67.14%) patients having significant stenosis in the main trunk and/or one or more major branches. Overall, 23(16.43%) of the whole cohort of patients had multiple branch involvements in the three coronary artery territories. Conclusion: In patients aged up to 40 years with ischemic heart disease, significant coronary artery disease burden was seen, including a significant proportion with multi-vessel disease and a high level of branch involvement in all the principal epicardial coronary territories. This indicates a high burden of disease in a relatively young age group, with significant implications for long term management over and beyond reperfusion/revascularization efforts. Cardiovasc j 2022; 14(2): 103-110